(untitled) (World Economics and Finance Bulletin, 2022)
In 2020, a serious turn of events took place that altered history forever as a result by influencing several sectors of countries around the world in a negative manner. The international widespread of the covid-19 crisis came with little to no merits yet many negative impacts on a variety of aspects on an international scale, including but not limited to the fluctuating sudden slump in the crude oil prices that the world has witnessed. Despite the fact that simultaneity does not necessarily mean causality, however, the linkage between the international oil prices drops and the pandemic is evident according to expert commentators, and various researchers. Independently, the events of the occurrence of the COVID-19 pandemic and the collapse of the crude oil prices on an international level had a great impact on the sustainable economy. Finally, the increase in the positive COVID-19 cases contributed greatly to the fall of crude oil prices worldwide